Project Career REACH. Final Report 1983-84 - Parsippany - Troy Hills Board of Education, Parsippany, NJ.; Parsippany - Troy Hills Board of Education, Parsippany, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A career counseling project was undertaken to address the career decision-making needs of 12th-grade students identified as being non-goal oriented. A major part of the project was the establishment of a career resource center. Project activities consisted of planning, orientation, implementation, and evaluation. Planning activities included goal setting and clarification, developing means for student access to the center, developing administrative details, and establishing and selecting materials for the career resource center. Orientation involved personnel, teachers, administration, and students. Implementation focused on 106 students identified as those who could benefit most from individual career assessment and follow-up counseling. Activities in addition to individual counseling and career information services were an ongoing speaker program, field trips, and a career day. The center was well received and utilized by counselors, teachers, and students. The problem of student access due to limited free time was only partially solved. A manual for counselors was developed. Appendixes, amounting to over one-half of the report, include a fact sheet, a listing of monthly activities, an orientation presentation for counselors and teachers, questionnaire, correspondence and press releases, forms used in the project, and a short bibliography. (YLB)
Sponsoring Agency: New Jersey State Dept. of Education, Trenton. Div. of Vocational Education and Career Preparation.
ERIC Note: Parts of this document contain light, broken type.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; Career Counseling; Career Education; Career Planning; Counseling Services; Decision Making; Goal Orientation; Grade 12.; High Schools; Program Development; Program Evaluation; Program Implementation; Resource Centers; Reports, Descriptive